English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3x + 4y = 6
y = 2x – 4

2007-06-03 10:26:12 · 5 answers · asked by A 1 in Science & Mathematics Mathematics

5 answers

3x + 4(2x - 4) = 6.

3x + 8x - 16 = 6.
11x = 22.
x = 2

3(2) + 4y = 6.

6 + 4y = 6.
4y = 0.
y = 0.

2007-06-03 10:30:20 · answer #1 · answered by Matthew H 2 · 0 0

3x + 4y = 6
y = 2x - 4
3x + 4(2x - 4) = 6
3x + 8x -16 = 6
11x -16 = 6
11x = 6 + 16
11x = 22
x = 22/11
x = 2 (wait, not done yet)
3x + 4y = 6
3(2) + 4y = 6
6 + 4y = 6
4y = 6-6 = 0
y = 0/4 = 0
to check: y = 2x - 4
(0) = 2(2) - 4?

2007-06-03 17:32:21 · answer #2 · answered by athos276 2 · 0 0

3x + 4y = 6
y = 2x – 4
Substitute 2x-4 for y in the 1st equation, getting:
3x +4(2x-4) = 6
3x +8x -16= 6
11x= 22
x = 2
y= 2x-4 = 2*2-4 = 0

2007-06-03 17:32:45 · answer #3 · answered by ironduke8159 7 · 0 0

3x +4(2x-4) = 6
3x + 8x -16 =6
11x = 22
x=2

3(2) +4y =6
6 + 4y= 6
4y =0
y=0

Answer x =2, y = 0.

2007-06-03 17:33:39 · answer #4 · answered by tgust660 1 · 0 0

3x + 4y = 6
(2x - y = 4) 4

11x=22
x = 2
y = 0

2007-06-03 17:33:34 · answer #5 · answered by FlashOfBlade(Dime Bros) 5 · 0 0

fedest.com, questions and answers